Respuesta :
I multiply second equation by 2 which becomes -4x+ 6y=8 and for y I multiply second equation by 3 which becomes -6x+9y=12
To eliminate the variable y, we will multiply equation 1 by 1 and equation 2 by 3 and add
To eliminate the variable x, we will multiply equation 2 by 1 and equation 1 by 2 and add the result
Given the system of equations;
4x-9y = 7 ........ 1 * 1
-2x+ 3y= 4 ....... 2 * 2
We will eliminate variables using the elimination method
To eliminate the variable x, we will multiply equation 2 by 1 and equation 1 by 2 and add the result to have:
4x-9y = 7
-4x+ 6y= 8
Adding both expressions
9y + 6y = 7 + 8
15y = 15
y = 15/15
y = 1
Similarly, To eliminate the variable y, we will multiply equation 1 by 1 and equation 2 by 3 and add the result to have:
4x-9y = 7
-6x+ 9y= 12
Adding both
4x - 6x = 7+ 12
2x = 19
x = 192
Learn more here: https://brainly.com/question/20160304